CHLORIDE AND WATER SOLUBILITY IN BASALT AND ANDESITE MELTS AND IMPLICATIONS FOR MAGMATIC DEGASSING - Webster J.D.; Kinzler R.J.; Mathez E.A. (My University, 1999)
The solubilities of chloride (Cl−) and H2O in aluminosilicate melts of basalt, andesite, and latite compositions saturated in aqueous vapor and/or hydrosaline liquid were determined at 2000 bars and ≈1 bar by melting mixtures of NaCl, KCl, H2O, and natural and synthetic rock powders and by measuring Cl− and H2O in the run product glasses. The abundances of Cl− in several of the aqueous run product liquids were also measured, and the partitioning of Cl− between aqueous vapor and silicate melt was determined for these experiments.